Performance evaluation of novel fluorescent-based lateral flow immunoassay (LFIA) for rapid detection and quantification of total anti-SARS-CoV-2 S-RBD binding antibodies in infected individuals. (May 2022) - Shurrab, Farah M.; Younes, Nadin; Al-Sadeq, Duaa W.; Liu, Na; Qotba, Hamda; Abu-Raddad, Laith J.; Nasrallah, Gheyath K.
Highlights: Finecare fluorescence lateral flow immunoassay (LFIA) test quantitatively detects SARS-CoV-2 spike protein receptor-binding domain (S-RBD) total antibodies. Finecare test showed 92% sensitivity and 100% specificity. Finecare test strongly correlates with surrogate virus-neutralizing test (sVNT) and automated assays. Finecare test can be used to predict the amount of neutralizing antibodies. Abstract: Background: A vast majority of the commercially available lateral flow immunoassay (LFIA) is used to detect SARS-CoV-2 antibodies qualitatively. Recently, a novel fluorescence-based lateral flow immunoassay (LFIA) test was developed for quantitative measurement of the total binding antibody units (BAUs) (BAU/mL) against SARS-CoV-2 spike protein receptor-binding domain (S-RBD). Aim: This study aimed to evaluate the performance of the fluorescence LFIA Finecare TM 2019-nCoV S-RBD test along with its reader (Model No.: FS-113). Methods: Plasma from 150 reverse trancriptase–PCR (RT-PCR)-confirmed positive individuals and 100 prepandemic samples were tested by Fincare TM to access sensitivity and specificity. For qualitative and quantitative validation of the FinCare TM measurements, BAU/mL results of FinCare TM were compared with results of 2 reference assays: the surrogate virus-neutralizing test (sVNT, GenScript Biotech, USA) and the VIDAS®3 automated assay (BioMérieux, France). Results: Finecare TM showed 92% sensitivity and 100% specificity compared with PCR. Cohen's Kappa statistic denoted moderate and excellent agreement with sVNT and VIDAS®3, with values being 0.557 (95% CI: 0.32–0.78) and 0.731 (95% CI: 0.51–0.95), respectively. A strong correlation was observed between Finecare TM /sVNT ( r = 0.7, p < 0.0001) and Finecare TM /VIDAS®3 ( r = 0.8, p < 0.0001). Conclusion: Finecare TM is a reliable assay and can be used as a surrogate to assess binding and neutralizing antibody response after infection or vaccination, particularly in none or small laboratory settings.